Estratégias de planejamento ambiental na Ilha do Príncipe: subsídios para gestão local integrada - Miranda, Lúcio Correia (2016)
In the last three years, the Principe Island has undergone socio-cultural and environmental transformations, a unique time in its history after the colonial period, due to the current political and economic structure supported on the tourism exploitation based on the resorts enlargement, mainly located in its northern region. These changes have boosted socio-environmental impacts, including those triggered by the relocation of communities in absence of integrated planning, intensification of coastal erosion through increasing demand for the exploitation of sand and the expansion of inhabited areas spontaneously, which has greatly aggravated the loss of local basic sanitation. The objective of this study was to investigate strategies and practices of environmental planning on Prince’s Island, based on the geoecological approach, aiming at subsidizing the construction of sustainable environmental management. It consists of a qualitativequantitative approach, resulting from the assumption that planning and environmental management are normative instruments that guide sustainable environmental management, built collectively through dialogue between the public authorities, related non-governmental organizations and local communities involved. However, when formulated and implemented through centralized decisions they promote the multiplication of socio-environmental impacts, creating, even, obstacles to the development of traditional livelihood activities. In addition to discussing the need to think about environmental management from the socio-spatial, cultural and ecological aspects, contributions are also made to the planning and management systems of the Island environment, in particular, the Prince’s Island, highlighting its socioecological particularity as a limiting factor and potentiator of local development. Based on theoretical and methodological orientations of the Geoecology of Landscapes, it is constituted by a holistic and integrated study that will encourage, at the heart of environmental management, and dialogical interactions among different spheres of society. In order to achieve the proposed objective, apart from the bibliographical and cartographic survey, we proceeded with the Geoprocessing for the qualification of the landscape state and dialogues with the fishing, farming and urban communities. In this way, besides presenting cartography on the physical-natural aspects of the island, maps of land use and occupation were produced, geoecological zoning, ecodynamic zoning, functional zoning, both on the scale of 1:50,000, among others, maps of the Landscape Physiognomy of the city of Santo António on the scale of 1:7,000 and evolution of the city of Santo António, on the scale of 1:20,000. It can be seen that, in the nuances of development pursued by local environmental management policies Socio-environmental sustainability remains at the merely discursive level, in view of the Centralized and generalist environmental management, which is far from the Sociocultural and ecological specificities of the insular environmental system.